A counseling service for developing the qona'ah attitude of millennial generation in attaining happiness - Halik, Al (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
Purpose - The research objective is a trial to create group counseling services with self-acceptance techniques to develop Qona’ah attitudes in realizing the happiness of the millennial generation.Method - The method used in data collection was a literature study.Result - The result of this paper is to offer group guidance and counseling using self-acceptance techniques to develop a Qona’ah attitude. Positive self-acceptance will be able to create happiness.Implications - Qona’ah attitude requires a training with strong patience, the applied counseling services are group guidance and counseling services with four stages.Originality - A method of developing the Qona’ah attitude of the millennial generation is a process of providing professional assistance which is characterized by a continuous process with systematic steps to an individu or groups of people.